Determinants of AI Innovation Adoption in Banking Services: Mediating Role of Attitude among Young Generations - Lily Purwianti; Ella Kristia; Lady; Hepy Hefri Ariyanto (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2026)
Background: Integration of AI technology in the banking sector is growing rapidly, but adoption remains relatively low due to users' concerns regarding awareness, privacy, and security. This situation necessitated the exploration of how an expanded version of the Technology Acceptance Model (TAM) model influenced AI adoption, particularly among younger generations. Purpose: This research aimed to examine how awareness, perceived security, and ease of use could directly influence AI adoption through attitude as a mediator. Method: A quantitative survey was carried out among 418 bank customers from BCA, BNI, BRI, Mandiri, and OCBC in Indonesia who had used AI-based banking services, and the data were analyzed using PLS-SEM. Findings: Awareness, perceived security, and ease of use strongly influenced the intention to adopt AI, both directly and through a mediating effect. Furthermore, Generation Y was more affected by ease of use and security than Generation Z. Conclusions: All variables were found to significantly influence the willingness to adopt AI, with attitude serving as a mediating factor. Research implication: This research strengthened the TAM model by integrating ease of use, security, and awareness variables, as well as focusing on generational differences in technology adoption.